Studies of some Interesting Diseases of Rauvolfia serpentina from India. I. Contribution to the Knowledge of Disease Development in Relation to Environment - Mehrotra, Madhava D. (Indian Forester, 1976)
Three interesting foliage diseases of Rauvolfia serpentina caused by Phomopsis sethii Macrophomia paseolina and Mycosphaerella rauwolfiae have been reported and the influence or environal conditions upon disease development has been emphasized. P.sethii is new to science and M. phaseolina is reported for the first time to occur on R.serpentina in India. P.sethii caused little damage to the host whereas the other two pathogens were quite destructive. M.phaseolina was found associated with drying and dead branches besides inflorescences which were eventually dropped-off resulting in heavy loss to seed production during humid months from July to September.